2019
DOI: 10.1096/fj.201900642r
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte exosomes activate neutrophils and enhance skin inflammation in psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease that severely affects patients physiologically and psychologically. The pathogenesis involving communication between psoriatic keratinocytes and infiltrated immune cells such as neutrophils remains unclear. Exosomes are emerging mediators of intercellular communication. Herein we aim to investigate the release and function of psoriatic keratinocyte exosomes, which have not been illustrated to any extent. We first isolated exosomes from both healthy and psoriasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 57 publications
3
95
0
1
Order By: Relevance
“…Keratinocyte-derived exosomes can affect the dendritic cell phenotype and cytokine production [81]. Cytokine-treated keratinocytes secrete exosomes that promote neutrophil pro-inflammatory factor production, including IL-6, IL-8, and TNF-α [82].…”
Section: Keratinocyte Crosstalk With Immune Cells Via Extracellular Vmentioning
confidence: 99%
“…Keratinocyte-derived exosomes can affect the dendritic cell phenotype and cytokine production [81]. Cytokine-treated keratinocytes secrete exosomes that promote neutrophil pro-inflammatory factor production, including IL-6, IL-8, and TNF-α [82].…”
Section: Keratinocyte Crosstalk With Immune Cells Via Extracellular Vmentioning
confidence: 99%
“…As one early study revealed, IFN-α induced mast cells to release EVs that were capable of transferring cytoplasmic PLA2 activity to neighboring CD1a-expressing cells, which further led to the generation of neolipid antigens and subsequent recognition by CD1a-reactive T cells 11 , which established EVs as critical mediators in psoriasis. Our recent study demonstrated that EVs isolated from psoriatic cytokine-induced keratinocytes could be endocytosed by neutrophils and induced the latter to produce NETs and pro-inflammatory cytokines, thus exacerbating psoriatic inflammation 12 . Interestingly, neutrophils from patients with generalized pustular psoriasis secreted more EVs than those from controls, and further triggered keratinocytes to produce high levels of inflammatory molecules, such as IL-1β, IL-36G, IL-18 and TNF-α 82 .…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%
“…Recent work from us and others has indicated that EVs play key immunomodulatory roles in the pathogenesis of various inflammatory skin diseases, such as psoriasis 11 , 12 , atopic dermatitis (AD) 13 , lichen planus (LP) 14 , bullous pemphigoid (BP) 15 , systemic lupus erythematosus (SLE) 16 , and chronic wound healing 7 . These inflammatory skin disorders pose major problems in dermatology given their complex pathophysiology and refractory nature, which ultimately pose a burden to the health, economic and social systems.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Jiang et al investigated the release and function of psoriatic keratinocyte-EXs and focused on the communication between keratinocytes and neutrophils [81]. In order to simulate psoriasis condition, keratinocytes were treated with psoriatic cytokine cocktail and then released exosomes from both healthy and psoriatic keratinocytes were characterized.…”
Section: Cross-talk Between Keratinocytes and Immune Cells Through Evsmentioning
confidence: 99%
“…IL-8 is able to attract more neutrophils to the lesion site [82] and TNF-α can be found in many inflammatory diseases including psoriasis [84]. However, a specific cargo in psoriatic keratinocyte-EXs that might be responsible for stimulating the activation of neutrophils was not identified [81]. On the other hand, NF-kB and p38 MAPK signaling pathways were activated in neutrophils, induced by cytokine-treated keratinocyte-EXs and were responsible for the expressions of mentioned proinflammatory factors.…”
Section: Cross-talk Between Keratinocytes and Immune Cells Through Evsmentioning
confidence: 99%